Explaining the influence of biophilic design on employee well-being - Carmen Valor; Raquel Redondo; Isabel Carrero (Scientific Reports)
Abstract Biophilic workplace design has been proposed as an effective strategy to increase employee well-being in open-plan offices. To expand our understanding of why and for whom indoor nature exposure increases well-being, the aim of this study was to evaluate vigor as a mediator and to examine whether nature relatedness is a direct antecedent of nature exposure or a moderator of the relationship between exposure to nature and vigor. Based on longitudinal data obtained from a two-wave panel design with white-collar workers in open-plan offices (Study 1, n = 345; Study 2, n = 291), using a rival model strategy and two dependent variables, i.e., job well-being and overall well-being, this study revealed that nature relatedness is a direct antecedent of nature exposure and that vigor mediates the relationship between nature exposure and the examined outcomes. These results indicate that although natural exposure increases employee well-being, the effects are indirectly driven by employees’ connection with nature. These findings have implications for the implementation of biophilic workplace design.